2010
DOI: 10.1007/s10753-010-9236-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Farnesylthiosalicylic Acid on Mediators Release by Mast Cells: Preferential Inhibition of Prostaglandin D2 and Tumor Necrosis Factor-α Release

Abstract: There is substantial evidence suggesting that the Ras inhibitor farnesylthiosalicylic acid (FTS) may modulate various aspects of immune function and inflammation in addition to its well known anti-cancer activity. In this regard, we have recently shown that FTS suppresses T lymphocyte-mediated immune responses. Mast cells (MC), the main effector cells in the elicitation of the allergic response, are known to secrete granule-associated mediators and to release prostaglandins and cytokines on FCεRI-cross-linking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…These include the Ras inhibitor farnesylthiosalicylic acid, which reduces prostaglandin D 2 and TNF-α production [76]; chrysin, which decreases histamine, TNF-α, IL-1β, IL-4, and IL-6 production [77]; allergin-1, an immunoglobulinlike receptor expressed on mast cells [78]; and U63A05, a novel synthetic compound that inhibits Syk activation in mast cells and suppresses degranulation and TNF-α and IL-4 production [79].…”
Section: Development Of New Treatmentsmentioning
confidence: 99%
“…These include the Ras inhibitor farnesylthiosalicylic acid, which reduces prostaglandin D 2 and TNF-α production [76]; chrysin, which decreases histamine, TNF-α, IL-1β, IL-4, and IL-6 production [77]; allergin-1, an immunoglobulinlike receptor expressed on mast cells [78]; and U63A05, a novel synthetic compound that inhibits Syk activation in mast cells and suppresses degranulation and TNF-α and IL-4 production [79].…”
Section: Development Of New Treatmentsmentioning
confidence: 99%
“…Moreover, only SP concentrations higher than 1 μM were reported to be able to enhance the rate of oxygen consumption of isolated cardiac cell mitochondria 35 . Other authors had reported secretion of preformed TNF from mast cells in different species by different triggers 4, 36, 37 . However, there was no attempt to investigate how this secretion differs from de novo synthesis and release.…”
Section: Discussionmentioning
confidence: 99%
“…Ras proteins play an important role in cancer and in other biological phenomena, especially in activation of the immune system . In lymphocytes, Ras proteins regulate signalling downstream of the antigen receptor, as well as the secretion, adhesion and proliferation of cytokines .…”
Section: Discussionmentioning
confidence: 99%